Expression analysis of SOX2 and SOX9 in patients with oral squamous cell carcinoma - Steen, Sonja; Horn, Dominik; Flechtenmacher, Christa; Hoffmann, Jürgen; Freier, Kolja; Ristow, Oliver; Heß, Jochen; Moratin, Julius (Head & neck, 2024)
Background: Lately SOX2 and SOX9, transcription factors associated with stemness-like phenotypes of cancer cells, have been linked to tumor growth, metastasis, and resistance to therapy. Methods: This study aimed on evaluating the expression of SOX2 and SOX9 in a large cohort of patients with OSCC including primary and recurrent tumors and corresponding lymph node metastases. Semiautomatic digital pathology scoring was used to determine protein expression and survival analysis was performed to evaluate its prognostic significance. Results: We found a significant downregulation of SOX9 from primary disease to lymph node metastases (p < 0.001). SOX9 expression and the subgroup SOX2lowSOX9high were significantly correlated with worse overall survival (p < 0.05). Additionally, SOX2lowSOX9high expression pattern was confirmed as independent prognosticator for overall survival. Conclusions: These results indicate the relevant role of SOX2 and SOX9 in patients with OSCC and show the clinical relevance for further investigation on the molecular mechanisms underlying SOX-related gene expression.